Respuesta :
I'll solve it by substitution instead of graphing.
x + y = 2
y = (1/2)x + 5
Substitute equation 2 into equation 1.
x + (1/2)x + 5= 2
(3/2)x + 5 = 2
(3/2)x + 5 - 5 = 2 - 5
(3/2)x = -3
(2/3) * (3/2)x = -3 * (2/3)
x = -2
x + y = 2
-2 + y = 2
y - 2 = 2
y - 2 + 2 = 2 + 2
y = 4
x = -2
y = 4
(-2,4)
Your answer is B) (-2,4).
x + y = 2
y = (1/2)x + 5
Substitute equation 2 into equation 1.
x + (1/2)x + 5= 2
(3/2)x + 5 = 2
(3/2)x + 5 - 5 = 2 - 5
(3/2)x = -3
(2/3) * (3/2)x = -3 * (2/3)
x = -2
x + y = 2
-2 + y = 2
y - 2 = 2
y - 2 + 2 = 2 + 2
y = 4
x = -2
y = 4
(-2,4)
Your answer is B) (-2,4).